2006
DOI: 10.1021/ma051776t
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of Initiated Chemical Vapor Deposition of Polymers:  Analyses of Deposition Rate and Molecular Weight

Abstract: This work studies the effects of changing equilibrium monomer surface concentration on the deposition rates and the number-average molecular weights (M n) of polymers deposited from glycidyl methacrylate and cyclohexyl methacrylate using initiated chemical vapor deposition (iCVD) with tert-butyl peroxide as the initiator. Both the surface temperature and the monomer partial pressure were varied to effect different equilibrium surface concentrations, measured using a quartz-crystal microbalance. In either case,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Previous studies have shown that the deposition rate and the number-average molecular weight in the i-CVD process are linearly dependent on the monomer surface concentration, 12 pointing out a polymerization process predominantly occurring at the substrate surface. The monomer surface concentration can be related to a nondimensional parameter given by the ratio of the monomer partial pressure (P M ) and its saturated vapor pressure (P sat ), P M /P sat .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that the deposition rate and the number-average molecular weight in the i-CVD process are linearly dependent on the monomer surface concentration, 12 pointing out a polymerization process predominantly occurring at the substrate surface. The monomer surface concentration can be related to a nondimensional parameter given by the ratio of the monomer partial pressure (P M ) and its saturated vapor pressure (P sat ), P M /P sat .…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of in situ real-time diagnostics in order to define an i-CVD process window is, therefore, fundamental. So far, in literature, quartz crystal microbalance (QCM) measurements have been used for the determination of the monomer surface concentration, [12][13][14] while the film growth development has been followed by means of laser interferometry. [15][16][17][18] During QCM measurements, the mass adsorption on the quartz crystal, generally gold coated, results in a frequency shift that can be directly related to the mass of the adsorbed monomer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations